Best practices in natural childbirth care (Research, Society and Development, 2021)
The development of good practices in assisting normal childbirth, implemented in the routines of obstetric centers, is important, considering the humanization of the maternal-fetal binomial, which favors a positive experience, as well as contributing to the parturition process so that the mother feels welcomed and can maintain physical and emotional health, ensuring an uncomplicated delivery and that brings good memories of that moment. The objective of this work was to evaluate what knowledge about the good practices adopted by nurses who work in assisting natural childbirth, according to scientific publications. The integrative research method was used, in which 11 scientific articles made available in full, in the last 5 years, selected in the Virtual Health Library (VHL), comprised the analyzed sample. The results showed that in all publications good care practices were used, especially non-pharmacological ones by nurses for pain relief and providing physiological and humanized labor. We conclude that the strategies employed by nurses contribute to the rescue of natural childbirth, which has numerous advantages for the mother and child binomial.